The Effect of Insulin Treatment on the Balance between Tissue Plasminogen Activator and Plasminogen Activator Inhibitor-1 in Type 2 Diabetic Patients - Vukovich, Thomas; Proidl, Sylvia; Knöbl, Paul; Teufelsbauer, Harald; Schnack, Christoph; Schernthaner, Guntram (Thrombosis and Haemostasis, 1992)
Beside hypercoagulation and hyperactivated platelets disturbances of the fibrinolytic system towards hypofibrinolysis have been reported to be associated with both glycemic and lipidemic derangement in diabetic patients. In the present prospective follow-up study the effect of 16 weeks insulin treatment and glycemic regulation on plasma levels of tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1), the main regulators of fibrinolysis, was investigated in 19 type-2 diabetic patients with secondary failure to sulphonylureas. A similar glycemic regulation was obtained in a control group of 10 type 2 diabetic patients with sufficient metabolic response to strict dietary treatment and continuation of sulphonylurea treatment. Compared to 27 healthy subjects levels of tPA and PAI-1 were not significantly increased in type 2 diabetic patients before metabolic intervention. Although a hypofibrinolytic state due to an increase of PAI-1 levels was previously reported in obese hyperinsulinemic patients, no effect of insulin treatment on both tPA- and PAI-1 levels was observed in the present study including patients with only slightly increased body mass index (median 26.0 kg/m2). By correlation analysis PAI-1 levels were significantly related to serum cholesterol (R = 0.52) and glycemic control (glucose R = 0.41) in the whole group of diabetic patients at entry and in both subgroups after 16 weeks of treatment (insulin group: cholesterol R = 0.46, HbA1c R = 0.51; sulphonylurea group: cholesterol R = 0.59, HbA1c R = 0.58). In healthy subjects tPA and PAI-1 was correlated to serum insulin (R = 0.54, R = 0.56) and triglycerides (R = 0.46, R = 0.40). In conclusion, our results indicate that insulin treatment associated with metabolic improvement has no adverse effect to fibrinolysis in type 2 diabetic patients.